How to dig a hole to the other side of the world - McNulty, Faith; Simont, Marc. (New York : Scholastic, 1990)
A child takes an imaginary 8,000-mile journey through the earth and discovers what's inside.
K
b
b
Keywords: Earth (Planet) -- Internal structure -- Juvenile literature; Earth (Planet) -- Internal structure